Novel FtsZ inhibitor with potent activity against Staphylococcus aureus. (11th August 2021) - Kumar, Manoj; Mathur, Tarun; Barman, Tarani Kanta; Chaira, Tridib; Kumar, Ram; Joshi, Vattan; Pandya, Manisha; Sharma, Lalima; Fujii, Kunihiko; Bandgar, Mahadev; Jadhav, Balasaheb; Bambal, Ramesh; et al.
Abstract: Objectives: FtsZ is an essential bacterial protein and an unexplored target for the development of antibacterial drugs. The development of a novel inhibitor targeting FtsZ offers a potential opportunity to combat drug resistance. DS01750413, a new derivative of PC190723, is a novel FtsZ inhibitor with improved in vitro and in vivo activity. The objective of this study was to investigate the efficacy of DS01750413 against Staphylococcus spp., including MRSA, in in vitro and in vivo models. Methods: In vitro activities of DS01750413 and standard-of-care antibiotics were evaluated against clinical isolates of Gram-positive pathogens. The in vivo efficacy was evaluated in a murine systemic infection model caused by MRSA. Results: DS01750413 showed potent in vitro activity against MRSA clinical isolates with MIC ranges of 0.5–1 mg/L and also demonstrated concentration-dependent bactericidal killing. In the murine bacteraemia infection model of MRSA, treatment with DS01750413 resulted in prolonged survival of animals compared with placebo-treated animals and exhibited a significant reduction in the bacterial load in liver, spleen, lungs and kidneys. Conclusions: DS01750413 showed encouraging in vitro and in vivo activity against MRSA. As a novel chemical class, DS01750413 has the potential to become clinically viable antibiotics to address the drug resistance problem by its unique novel targeting mechanism of action.